Vantagem e desvantagem competitiva: os construtos e a métrica - Vasconcelos, Flávio Carvalho de (2009)
Despite ubiquitous in strategy and related fields, the concept of competitive advantage continues to be under debate in the academy still lacking a precise and widely accepted definition. A manifestation of this situation is the current debate about its philosophical grounds and the questioning of its own existence. This paper offers a constitutive definition that allows an operationalization of the concept and the development of metric for the competitive advantage. This metric is applied to a sample of 2805 firms in 16 countries with a total of 13,259 observations. The analysis indicates the occurrence of competitive advantage in 10 to 12% of the firms with a similar percentage showing a competitive disadvantage. It demonstrates that the occurrence of competitive advantage is not a rare event. A statistical test is proposed to verify its statistical significance.